Analys av nötningsfenomen i pappersbaserat friktionsmaterial för våta kopplingar - Lantz, Maja (2011)
Wet clutches are used in automatic transmissions to transmit torque and enable gear changes. The primary component of a wet clutch is the paper-based friction disc and steel separator disc immersed in transmission uid. Volvo Construction Equipment (Volvo CE) develop and build automatic powershift-transmissions with wet clutches for use in their heavy-duty equipment. Volvo CE and Luleå University of Technology (LTU) conduct research on wet clutches which involves paper-based friction materials. The two most common materials in production, material A and B, were tested in a wet clutch test rig at LTU. The tests showed a wear phenomenon in material A where the wear rate at a inection point signicantly increases. This work examines what might have happened with the material and if material B shows the same phenomenon. After the test run with material B it appeared to have a hint of the same phenomenon, but only after about 5 000 more cycles then for material A. Analysis of optical and scanning electron microscope, elemental analysis, oil absorption test, analysis of temperature and friction coecient history and comparisons of the materials dierent compositions were carried out. It turned out that material A is more permeable than material B, which is virtually impenetrable. Material B was subjected to more than twice as many cycles as material A before the same degree of mass loss occurred. During wear the bers agglomerates in each material, at a higher degree in material B then in material A. Material A may have been glazed and/or carbonized and that could have made the material brittle and fragile and at an inection point to such an extent that the wear rate increased. Validerat; 20110921 (anonymous)